The ceramide-S1P pathway as a druggable target to alleviate peripheral neuropathic pain. (1st September 2020) - Langeslag, Michiel; Kress, Michaela
ABSTRACT: Introduction: Neuropathic pain disorders are diverse, and the currently available therapies are ineffective in the majority of cases. Therefore, there is a major need for gaining novel mechanistic insights and developing new treatment strategies for neuropathic pain. Areas covered: We performed an in-depth literature search on the molecular mechanisms and systemic importance of the ceramide-to-S1P rheostat regulating neuron function and neuroimmune interactions in the development of neuropathic pain. Expert opinion: The S1P receptor modulator FTY720 (fingolimod, Gilenya®), LPA receptor antagonists and several mechanistically related compounds in clinical development raise great expectations for treating neuropathic pain disorders. Research on S1P receptors, S1P receptor modulators or SPHK inhibitors with distinct selectivity, pharmacokinetics and safety must provide more mechanistic insight into whether they may qualify as useful treatment options for neuropathic pain disorders. The functional relevance of genetic variations within the ceramide-to-S1P rheostat should be explored for an enhanced understanding of neuropathic pain pathogenesis. The ceramide-to-S1P rheostat is emerging as a critically important regulator hub of neuroimmune interactions along the pain pathway, and improved mechanistic insight is required to develop more precise and effective drug treatment options for patients suffering from neuropathic pain disorders.